2021
DOI: 10.1002/ecy.3320
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove growth response to experimental warming is greatest near the range limit in northeast Florida

Abstract: Shrubs are invading into grasslands around the world, but we don’t yet know how these shrubs will fare in a warmer future. In ecotonal coastal wetland ecosystems, woody mangroves are encroaching into herbaceous salt marshes owing to changes in temperature, precipitation, and sediment dynamics. Increasing mangrove biomass in wetlands often increases carbon storage, which is high in these productive ecosystems, but little is known about how mangrove growth will change in response to warming. To address this know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…In our experiment, the southern site (SS) was near an inlet and thus closer to the open ocean while the northern site (NS) was further from the ocean and closer to freshwater inputs. As a result, salinity tends to be higher at SS than at NS (Chapman et al, 2021). Previous work at SS has also indicated that salinity can be very high during summer (up to 60 ppt) and lower during winter (48 ppt) (Dangremond et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our experiment, the southern site (SS) was near an inlet and thus closer to the open ocean while the northern site (NS) was further from the ocean and closer to freshwater inputs. As a result, salinity tends to be higher at SS than at NS (Chapman et al, 2021). Previous work at SS has also indicated that salinity can be very high during summer (up to 60 ppt) and lower during winter (48 ppt) (Dangremond et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The south site (SS) was located roughly 20 km south of St. Augustine (34 km to the south of NS) and just north of the Matanzas Inlet (29°43'38.3"N, 81°14'25.0"W). NS and SS have similar elevations, and average annual precipitation at the GTMNERR reserve is 1317 mm (Chapman et al, 2021). Mean annual temperature (2001–2018) at St. Augustine is 20.8°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Site characteristics of Guana Tolomato Matanzas ResearchReserve along the northeastern coast of Florida. Shown with permission fromChapman et al 2021 …”
mentioning
confidence: 99%